Population-based epidemiology of 9767 ankle fractures. Issue 1 (February 2018) - Elsoe, Rasmus; Ostgaard, Svend E.; Larsen, Peter
Highlights: The literature lacks large-scale and recent population-based epidemiological studies of ankle fractures including all fractures and age groups based on accurate population sizes. The present study shows an incidence of 168.7/100, 000/year from a non-selected patient group with ankle fractures, spanning a decade. The present study includes all ankle fractures and is based on an accurate population size. Abstract: Background: The purpose was to provide up-to-date information concerning the incidence of ankle fractures in a large and complete population including all age groups, spanning a decade, and report the distribution of fractures, trauma mechanism and patient baseline demographics. Methods: Population-based epidemiological study of all patients treated for an ankle fracture in a 10-year period from 2005 to 2014. Results: A total of 9767 patients with ankle fractures were treated between 2005 and 2014. The mean age at time of fracture was 41.4 (24.3 SD) years. The mean incidence of ankle fractures between 2005 and 2014 was 168.7/100, 000/year. Years with cold winters showed increased incidences compared with years with normal winters. For males, the incidence was 157.1/100, 000/year, and for females, 179.5/100, 000/year. The incidence shows a peak incidence among adolescents in both genders with a male predominance. After the age of 19 the male incidence declines with age, which is in contrast to females, who experience an increasing incidence. The most common fracture type in all age groups was a fracture of the lateral malleolus representing 55% of all fractures. The predominant mode of injury was falls (61%) followed by sports (22%). Conclusion: This study shows an incidence of 168.7/100, 000/year spanning a decade. The most common fracture type in all age groups was a fracture of the lateral malleolus representing 55% of all fractures. The predominant mode of injury was falls (61%) followed by sports (22%).